2021
DOI: 10.2147/ndt.s308598
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and the Use of Cognitive Enhancers and Psychostimulants Among University Students: A Cross-Sectional Study

Abstract: Background University students, who are at risk of eating disorders (ED), are more liable to use cognitive enhancers and psychostimulants to improve their cognitive functions and lose weight. ED in Palestinian male students is a neglected health issue. We aimed to investigate the prevalence and the association between ED and cognitive enhancers, and psychostimulants use among An-Najah National University students (ANNU). Methods In a cross-sectional study conducted in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 80 publications
3
12
1
Order By: Relevance
“…Five studies [ 68 , 71 , 72 , 82 , 90 ] utilized two screening tools to assess FEDs symptomatology. Furthermore, one study was cross-sectional at two time points [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [ 68 , 71 , 72 , 82 , 90 ] utilized two screening tools to assess FEDs symptomatology. Furthermore, one study was cross-sectional at two time points [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Influence analysis was used to identify and eliminate outliers in our meta-analysis. Results of outliers’ analysis revealed that nine studies contributed with thirteen data points were mathematical outliers [ 65 , 66 , 71 , 72 , 78 , 81 , 82 , 87 , 90 ]. After removing all outlier studies, meta-analytic results revealed random-effects model of the prevalence of FEDs in medical students of 16.58% (95% CI 15.25–17.99%), heterogeneity Q = 72.71 (21) P < 0.0001, τ 2 = 0.03 (95% CI 0.01–0.11); τ = 0.18 (95% CI 0.12–0.33), I 2 = 71.1% (95% CI 55.6–81.2%); H = 1.86 (95% CI 1.50–2.31).…”
Section: Resultsmentioning
confidence: 99%
“… 65 Association between waterpipe smoking and eating disorders was also observed among Palestinians in a previous study. 66 This association could indicate that waterpipe smoking could be associated with unhealthy food behaviours for weight loss among Palestinians. Further investigation is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…72 A previous local study demonstrated that chocolate consumption was associated with decreased risk of eating disorders among young Palestinians. 66 It has been found that there is a relationship between guilt feeling when eating chocolate and developing abnormal eating behaviours; the high the guilt score, the more tendency to report symptoms such as binging and vomiting. 73 This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, 19.2% of Lithuanian higher-education students during emerging adulthood were at risk for ED. The results of the similar positive pre-pandemic ED screenings (from 16% to 33%) can be observed in the student populations in Nigeria [ 56 ], Lebanon [ 57 ], Singapore [ 58 ], Spain [ 59 ], Palestine [ 60 ], Pakistan [ 61 ], Turkey [ 62 ], Bangladesh [ 63 ], Iran [ 64 , 65 ], the United Arab Emirates [ 66 ], and Egypt [ 67 ]. Meanwhile, significantly lower pre-pandemic reports of the prevalence of the ED risk among students ranging from 4.5% to 14.9% were identified in the countries such as Poland [ 68 ], Croatia [ 69 ], the United States [ 70 , 71 ], Puerto Rico [ 72 ], Brazil [ 73 ], China [ 74 , 75 ], Japan [ 76 ], South India [ 29 ], and Malaysia [ 77 ].…”
Section: Discussionmentioning
confidence: 76%